Respostas

2014-08-13T09:33:19-03:00
Em cada caso a seguir,faltam parênteses, coloque-os para obter os resultados desejados:a)10-2.3+1=2 b)10-2.3+1=25  c)72+60:12-8=87  d)72+60:12-8=3


a)10-2.3+1=2 

  10 - 2.(3 + 1) =2 
  10 - 2 (   4)   = 2
  10 -    8       = 2
        2           = 2


b)10-2.3+1=25

(10 - 2).3 + 1 = 25
(   8   ).3  + 1 = 25
      24     + 1 = 25
            25    = 25  


c)72+60:12-8=87

72 + 60 : 12 - 8 = 87
72 + 60 :(12-8) = 87
72 +  60  :  4    = 87
72 +      15      = 87
        87          = 87


d)72+60:12-8=3

(72 + 60) : 12 - 8 = 3
      132   : 12 - 8 = 3
              11   - 8 = 3
                   3    = 3
1 4 1